Influence of osteocytes in the in vitro and in vivo β‐tricalcium phosphate‐stimulated osteogenesis. Issue 8 (30th September 2013) - Chen, Zetao; Wu, Chengtie; Yuen, Jones; Klein, Travis; Crawford, Ross; Xiao, Yin
Abstract Osteocytes, known to act as the main regulators of bone homeostasis, have become a major focus in the field of bone research. Bioactive ceramics have been widely used for bone regeneration. However, there are few studies about the interaction of osteocytes with bioceramics. The effects of osteocytes on the in vitro and in vivo osteogenesis of bioceramics are also unclear. The aim of this study was to investigate the role of osteocytes on the β‐tricalcium phosphate (β‐TCP) stimulated osteogenesis. It was found that osteocytes responded to the β‐TCP stimulation, leading to the release of Wnt (wingless‐related MMTV integration site), which enhanced osteogenic differentiation of bone marrow stromal cells via Wnt signaling pathway. Receptor activator of nuclear factor kappa B ligand, an osteoclast inducer, was also upregulated, indicating that osteocytes would also participated in activation of osteoclasts, which played a major role in the degradation process of β‐TCP and new bone remodeling. In vivo studies further demonstrated that when the material was completely embedded by newly formed bone, the only cell contacting with the material was osteocyte. However, the material would eventually be degraded and replaced by the new bone, requiring the participation of osteoclasts and osteoblasts, which were demonstrated by using immunostaining in this study. As the only cell contacting with the material, osteocytes probably acted in a regulatory role to regulate the surrounding osteoclasts and osteoblasts. Osteocytes were also found to participate in the maturation of osteoblasts and the mineralization process of biomaterials, by upregulating E11 (podoplanin) and dentin matrix protein 1 expression. These findings indicated that osteocytes involved in bone biomaterial‐mediated osteogenesis and biomaterial degradation, providing valuable insights into the mechanism of material‐stimulated osteogenesis, and a novel strategy to optimize the evaluating system for the biological properties of biomaterials. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2813–2823, 2014.